The complexity of coding algorithms codes Lagrange - Кубицкий, В. И. (Problems of Informatization and Control, 2012)
Defined complexity (number of operations in finite fields) encoding algorithm of complete and incomplete Lagrange codes. A comparative analysis of different encryption algorithms for these codes.